PENTINGNYA SAKRAMEN BAPTIS BAGI KESELAMATAN MENURUT KATEKISMUS GEREJA KATOLIK - Pelealu, Omega Yasinta; Kaunang, Steward Louis Fransisko; Mandagie, Gerrardi Vincent Frederico (Department of Theology - Sekolah Tinggi Filsafat Seminari Pineleng, 2024)
This article discusses the Catholic Church's view of the Sacrament of Baptism as a sign and means of salvation for the faithful. The author developed his writing based on the theological ideas contained in the Catechism of the Catholic Church. So, based on official Church documents, the author attempts to explain that the sacrament of baptism is not only an entry point for Church membership but also that baptism offers spiritual fruits that are useful for the salvation of believers. By baptism, the people are united to Christ both in death and also in His resurrection. This is why the sacrament of Baptism still plays such an important role in the Catholic Church.